2015
DOI: 10.3329/uhj.v10i2.26124
|View full text |Cite
|
Sign up to set email alerts
|

Status of Lipid Profile among the Hypertensive Patients in Bangladesh

Abstract: Back ground: Hypertension and dyslipidemia are associated with oxidative stress and are major causes of cardiovascular disease amounting to 30% of global death rate. It is widely accepted that cardiovascular disease is associated with hypertension and increased blood levels of low-density lipoprotein (LDL), total cholesterol (TC), and triglycerides. In contrast, a low level of high density lipoprotein (HDL) is a risk factor for mortality from cardiovascular disease. Hypertension is a major public health proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Table 1 shows that mean age, height, weight, BMI were not statistically significant (p>0.05) between two groups, but mean systolic and diastolic blood pressure were significantly higher in hypertensive group than normotensive group. 13 study the results revealed that the mean value of serum total cholesterol, triglycerides and serum LDL-cholesterol was significantly higher and statistically significant. The mean of HDL of cases were lower than that of controls and was statistically significant.…”
Section: Bmi Circumference Was Calculated According To Western Pacifi...mentioning
confidence: 83%
See 1 more Smart Citation
“…Table 1 shows that mean age, height, weight, BMI were not statistically significant (p>0.05) between two groups, but mean systolic and diastolic blood pressure were significantly higher in hypertensive group than normotensive group. 13 study the results revealed that the mean value of serum total cholesterol, triglycerides and serum LDL-cholesterol was significantly higher and statistically significant. The mean of HDL of cases were lower than that of controls and was statistically significant.…”
Section: Bmi Circumference Was Calculated According To Western Pacifi...mentioning
confidence: 83%
“…DBP showed significant association with hypertensive patients (OR 1.7, 95% CI 0.33-3.29, P<0.05). In another study Forhad et al13 showedbinary logistic regression analysis showed total cholesterol was significantly associated with hypertensive patients Odds Ratio (OR) 1.20; 95% CI (0.97-1.38), p<0.001. Triglyceride and LDL-C was significantly associated with hypertensive patients (OR 1.29; 95% CI 0.91-1.41, p<0.001) and (OR 1.22; 95% CI 0.89-1.31, p<0.001) respectively.…”
mentioning
confidence: 96%